2020
DOI: 10.1038/s41598-020-64655-4
|View full text |Cite
|
Sign up to set email alerts
|

CNN-Peaks: ChIP-Seq peak detection pipeline using convolutional neural networks that imitate human visual inspection

Abstract: ChIP-seq is one of the core experimental resources available to understand genome-wide epigenetic interactions and identify the functional elements associated with diseases. The analysis of ChIP-seq data is important but poses a difficult computational challenge, due to the presence of irregular noise and bias on various levels. Although many peak-calling methods have been developed, the current computational tools still require, in some cases, human manual inspection using data visualization. However, the hug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 37 publications
0
15
0
Order By: Relevance
“…We also tested published datasets from Oh et al, who annotated peaks and noise for H3K27ac ChIP-seq in GM12878 cells and H3K4me3 in K562 cells 26 . Performance was generally consistent with our in-house labeled data, and though MACS2 performed slightly better than LanceOtron on sensitivity, LanceOtron outperformed MACS2 on precision, selectivity, and F1 score for both the H3K27ac data (LanceOtron GM12878 H3K27ac project)( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We also tested published datasets from Oh et al, who annotated peaks and noise for H3K27ac ChIP-seq in GM12878 cells and H3K4me3 in K562 cells 26 . Performance was generally consistent with our in-house labeled data, and though MACS2 performed slightly better than LanceOtron on sensitivity, LanceOtron outperformed MACS2 on precision, selectivity, and F1 score for both the H3K27ac data (LanceOtron GM12878 H3K27ac project)( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Tools such as DeepSea 24 and Bassett 25 take genomic sequence as input and can predict regulatory genomic features with high accuracy. Proof of principle studies have also shown promise for applying these techniques to peak calling 9,26 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here we compared the detection accuracy of ChIP-BIT2 to that of MACS2 (2020.4 version) [ 21 ] and CNN-Peaks [ 22 ]. MACS2 was widely used in ChIP-seq peak detection.…”
Section: Resultsmentioning
confidence: 99%
“…The computational results confirm the effectiveness of the indicators with 95% accuracy according to the official testing conformation report issued by G7. In addition, comparative analyses as presented in Table A1 demonstrate that our method achieves comparable performance (accuracy, precision and recall) in identifying crests and troughs of all three angular velocities than baseline models but requires quite less computation time than other baseline methods including multilayer perceptron (MLP) (Tang et al , 2015), convolutional neural network (CNN) (Oh et al , 2020), long short-term memory neural network (LSTM) (Laitala et al , 2020) and bidirectional LSTM (Bi-LSTM) (Hu et al , 2021). Actually, this advantage of computational efficiency is necessary for the implementation and adoption in real use for driving grading.…”
Section: Inertial Navigation System (Ins) Data-enabled Driving Behaviour and Road Smoothness Indicatorsmentioning
confidence: 96%